صيغة بيع العينة حقيقتها ومشروعيتها كما تجريها البنوك الإسلامية - Barg Eenb, Abubaker A Mohamed; Zakariyah, Habeebullah (Academic Journal of Research and Scientific Publishing, 2019)
من المسائل التي بحثها علماء المسلمين وتتعدد صورها في وقعنا ألمعاصر صيغة بيع العينة وهي أن يبيع الرجل سلعة بثمن مؤجل ثم يقوم المشتري ببيع السلعة نفسها على البائع بثمن حال أقل من الثمن الأول ويقبض الثمن. من البنوك التي تكثر من استخدام صيغة بيع العينة البنوك اإلسالمية في ماليزيا تحت بند صكوك البيع بالثمن الآجل وصكوك المرابحة والفرق بينهما في مدة الاستثمار وأجل الاستحقاق وصورتها أن يتقدم العميل للمصرف بطلب فيشتري المصرف منه أصلا بالثمن ثم يبيعه إليه بالأجل بمبلغ يزيد التمويل بمبلغ محدد بقيمة التمويل المطلوب وينقده عن ذلك بنسبة متفق عليها. وقد اختلف الفقهاء في حكم بيع العينة فذهب الجمهور إلى عدم جوازه وبطلانه، بينما ذهب الشافعية والظاهرية إلى جوازه، وهو ما استندت إليه البنوك ألماليزية وبعد تحرير الخلاف فإن القول الراجح هو قول الجمهور بعدم جواز صيغة بيع العينة وبطلان عقدها، فضلا عن عدم التزام البنوك الماليزية بالشروط التي وضعها الشافعي لجواز المعاملة ................................................................................................................................ Among issues being explored by Muslim scholars and its manifold in contemporary versions are of Forward Sale Contracts. The contract involves an individual selling a commodity or merchandise at deferred price then the buyer undertakes to sell the same commodity on conditional sale in future at price lower than initial price and peg the price. Islamic Banks in Malaysia are among the Islamic banks that frequently uses forward sale contract under instruments of Sukuk on deferred payment sale and Sukuk Murabahah. The difference between both is in the term of investment and maturity as well as the manner that the client of the Banks proceeds with funding requests in a specified amount which the Bank purchase from the client initially at the value of required funding and pegged the price and sell it back on deferred terms at increased amount thereon an agreed percentage. The Jurists have differed on the rulings of Forward Sale Contracts. Thus, the view of the majority is impermissibility or invalidity. However, Shafie and Zahiriyah are in favour of permissibility. This is the basis that the Malaysian Banks have relied upon. Further, after deliberation on the disputes, majority is in the opinion that the forward sale contract is not allowed and the contract is null and void. In addition, the Malaysian banks have not complied with the conditions set by Shafie for the permissibility of the transactions.